Optimal design of superelastic-friction base isolators for seismic protection of highway bridges against near-field earthquakes. - Ozbulut, Osman E.
The seismic response of a multi-span continuous bridge isolated with novel superelastic-friction base isolator (S-FBI) is investigated under near-field earthquakes. The isolation system consists of a flat steel-Teflon sliding bearing and a superelastic NiTi shape memory alloy (SMA) device. The key design parameters of an S-FBI system are the natural period of the isolated bridge, the yielding displacement of the SMA device, and the friction coefficient of the sliding bearings. The goal of this study is to obtain optimal values for each design parameter by performing sensitivity analysis of a bridge isolated by an S-FBI system. First, a three-span continuous bridge is modeled as two-degrees-of-freedom with the S-FBI system. A neuro-fuzzy model is used to capture rate- and temperature-dependent nonlinear behavior of the SMA device. Then, a set of nonlinear time history analyses of the isolated bridge is performed. The variation of the peak response quantities of interest is shown as a function of design parameters of the S-FBI system and the optimal values for each parameter are evaluated. Next, in order to assess the effectiveness of the S-FBI system, the response of the bridge isolated by the S-FBI system is compared with the response of the non-isolated bridge and the same bridge isolated by pure-friction (P-F) sliding isolation system. Finally, the influence of temperature variations on the performance of the S-FBI system is evaluated. The results show that the optimum design of a bridge with the S-FBI system can be achieved by a judicious specification of design parameters.
Keywords: Superelasticity; Structural control; Damper; Optimization; Shape memory alloy; Earthquake